Evolution of the crystal structure and magnetic properties of Sm-doped BiFeO3 ceramics across the phase boundary region. Issue 4 (15th February 2021) - Karpinsky, D.V.; Pakalniškis, A.; Niaura, G.; Zhaludkevich, D.V.; Zhaludkevich, A.L.; Latushka, S.I.; Silibin, M.; Serdechnova, M.; Garamus, V.M.; Lukowiak, A.; Stręk, W.; Kaya, M.; et al.
Abstract: Samarium doped BiFeO3 compounds having nano-size crystallites were prepared by the ethylene glycol assisted sol-gel synthesis method. X-ray diffraction and SEM measurements as well as Raman spectroscopy and FTIR experiments were used to clarify an evolution of the crystal structure on microscopic and local scale levels in the compounds having formula Bi1-x Smx FeO3, where 0 = x ≤ 1. Magnetization measurements along with the structural data were used to determine a correlation between magnetic properties and crystal structure of the compounds. The compounds with 0.1 = x ≤ 0.2 are characterized by the sequence of the structural transitions driven by the dopant increase, viz. from the polar rhombohedral phase to the non-polar orthorhombic phase via two-phase regions characterized by the presence of the anti-polar orthorhombic phase. The concentration regions ascribed to a coexistence of the rhombohedral and the anti-polar orthorhombic phases as well as the anti-polar orthorhombic and the non-polar orthorhombic phases are observed in the ranges 0.12 = x ≤ 0.15 and 0.15 < x < 0.18 respectively. The compounds having single phase rhombohedral structure are characterized by a release of remnant magnetization as compared to ceramics with similar chemical compositions but synthesized by the solid-state reaction method and having microscopic size crystallites. A correlation between the type of structural distortion, morphology of crystallites and an onset of remnant magnetization is discussed highlighting a difference in the evolution of crystal structure and magnetization observed for the Sm-doped ceramics prepared by modified sol-gel method and conventional solid-state reaction technique.